Temperature during vaccination shapes antibody responses and protection against infectious salmon anemia in Atlantic salmon under different prime–boost vaccine strategies - Manuel Soto-Dávila; Shona K. Whyte; Ruth L. Quispe; Yan-Ru Chen; Taylor Wheatley; Shawna L. Semple; Reza Ghanei-Motlagh; Eyesun Fajei; Eleanor Glahn; Frederick von Rönge; Andrew Swanson; Mark D. Fast (Fish & Shellfish Immunology, 2026)

Assessment of Salinity Tolerance in Lepeophtheirus salmonis Following Five Generations of Freshwater Treatment Selection - Reza Ghanei‐Motlagh; Shona K. Whyte; Manuel Soto‐Dávila; Eyesun Fajei; Maricruz Guevara; Amber F. Garber; Gro Vee; Preben R. Antonsen; Gordon Ritchie; Mark D. Fast (Journal of Fish Diseases, 2026)
Non‐medicinal approaches for controlling sea lice ( Lepeophtheirus salmonis ) infestations, such as freshwater (FW) treatments, have been increasingly implemented to support more sustainable parasite control in aquaculture. This study evaluated the efficacy of FW treatment against sea lice under controlled experimental conditions and assessed the potential development of resistance across multiple generations. Sea lice populations were maintained over five consecutive generations, and FW efficacy was evaluated by quantifying lice abundance on Atlantic salmon before and after treatment. Resistance assessment involved comparative bioassays using copepodid and adult life stages from two distinct populations, one exposed to FW and the other a saltwater (SW) control group. Our results demonstrated that a 4 h FW treatment significantly reduced total lice abundance, while an extended 18‐day exposure resulted in complete detachment of all lice from salmon. Importantly, bioassay comparisons revealed no evidence of resistance development, as both FW‐exposed and SW‐control populations maintained similar susceptibility across generations. The absence of measurable changes in salinity tolerance over multiple generations suggests that FW protocols may remain a viable and sustainable management strategy. However, the potential for genetic or epigenetic variation in FW tolerance among lice populations warrants further investigation to better understand long‐term implications for treatment efficacy.

Behavioural responses to heat in an arid-zone bird vary with thermal, hygric and social factors - J. R. D. Whyte; A. E. McKechnie; J. K. Crossley; S. J. Cunningham (Oecologia, 2026)
The severity of fitness costs resulting from behavioural trade-offs between heat dissipation and activities such as foraging is increasing with advancing climate change. In terrestrial habitats, shade and water may buffer individuals from the negative effects of heat exposure, as may load-lightening in group-living species. We tested the hypothesis that thermal and hygric properties of home ranges (shade and water availability) and social factors (group size) influence the costs associated with hot weather, using a population of white-browed sparrow-weavers ( Plocepasser mahali ) in the southern Kalahari Desert. Across all sparrow-weaver groups, heat avoidance (shade-seeking) and dissipation (panting) behaviours increased with increasing air temperature ( T air ), whereas foraging declined. Birds occupying shadier home ranges delayed the onset of panting to higher T air and foraged less while maintaining overall peck rates. Birds with access to water foraged more, maintained higher peck rates and sought shade at higher T air compared to birds without. However, they did not pant more, making the mechanism underpinning their increased foraging effort unclear. Birds in larger groups both panted more overall and sought shade at lower T air than birds in smaller groups but maintained similar overall peck rates. Taken together, these results suggest birds in shadier home ranges can forage more efficiently, buffering foraging costs at high T air . Our data therefore suggest that some impacts of increasing T air under climate change can be buffered by shade availability, but the impacts of water availability and social factors are less clear.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Methylation-based immune deconvolution in prostate cancer patients before and after radical prostatectomy - Lauren M. Hurwitz; Maeve Bailey-Whyte; Michael A. Daneshvar; Cathy D. Vocke; Julian Custer; Bríd M. Ryan; Stefan Ambs; Peter A. Pinto; Emily L. Rossi (Cancer Causes & Control, 2025)

Synergies of co-infecting pathogens, sea lice (Lepeophetheirus salmonis) and Moritella viscosa, are impacted by exposure order, and host response to initial infection - Wenlong Cai; Liang Zhong; Kathleen Parrish; Surendra Kumar; Khalil Eslamloo; Eyesun Fajei; Shona K. Whyte; Sara L. Purcell; Ladan Jahangiri; Runsheng Li; Albert Caballero Solares; Richard G. Taylor; et al. (Aquaculture, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

A comparative analysis of alternative splicing patterns in Atlantic salmon (Salmo salar) in response to Moritella viscosa and sea lice (Lepeophtheirus salmonis) infection - Shengnan Gao; Suxu Tan; Sara L. Purcell; Shona K. Whyte; Kathleen Parrish; Liang Zhong; Shucheng Zheng; Yuxuan Zhang; Ruoxi Zhu; Ladan Jahangiri; Runsheng Li; Mark D. Fast; et al. (Fish & Shellfish Immunology, 2024)

Transcriptome analysis revealed immune responses in the kidney of Atlantic salmon (Salmo salar) co-infected with sea lice (Lepeophtheirus salmonis) and infectious salmon anemia virus - Liang Zhong; Laura A. Carvalho; Shengnan Gao; Shona K. Whyte; Sara L. Purcell; Mark D. Fast; Wenlong Cai (Fish & Shellfish Immunology, 2023)

Correction to: Description of nest architecture and ecological notes on the bumblebee Bombus (Pyrobombus) lapponicus (Hymenoptera: Apidae: Bombini) - B. Martinet; K. Przybyla; J. Atkins; Y. Bosiger; D. Evrard; P. Gill; J. van Alphen; G. Whyte; P. Rasmont (Insectes Sociaux, 2022)

Description of nest architecture and ecological notes on the bumblebee Bombus (Pyrobombus) lapponicus (Hymenoptera: Apidae: Bombini) - B. Martinet; K. Przybyla; J. Atkins; Y. Bosiger; D. Evrard; P. Gill; J. van Alphen; G. Whyte; P. Rasmont (Insectes Sociaux, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hydrogen peroxide treatment and its impacts on Lepeophtheirus salmonis originating from the Bay of Fundy, Canada - Carter R. VanIderstine; Jordan D. Poley; Shona K. Whyte; Sara L. Purcell; Mark D. Fast (Journal of Fish Diseases, 2021)
Hydrogen peroxide (H 2 O 2 ) is used to treat sea lice infections of farmed salmonids in the Atlantic and Pacific Oceans and issues with resistance to this treatment, and others are a major threat to the sustainability of the industry. The objectives of this study were to determine how H 2 O 2 exposure affects survival and antioxidant‐related gene expression in salmon lice ( Lepeophtheirus salmonis ) collected from the Bay of Fundy, New Brunswick. The maximum recommended dose of H 2 O 2 is 1,800 mg/L, while the EC 50 values (with 95% CI) for the population tested were 1,486 (457, 2,515) mg/L for males and 2,126 (984, 3,268) mg/L for females. Neither temperature nor pretreatment with emamectin benzoate (EMB) impacted survival after H 2 O 2 exposure. RT‐qPCR was performed on pre‐adult sea lice exposed to H 2 O 2 and showed that four genes classically involved in the response to oxidative stress were unchanged between treated and control groups. Seven genes were found to be significantly upregulated in males and one in females. This is the first report on the efficacy and molecular responses of Atlantic Canada sea lice to H 2 O 2 treatment.

Microplastics in Commercially Important Small Pelagic Fish Species From South Africa - Adil Bakir; Carl D. van der Lingen; Fiona Preston-Whyte; Ashok Bali; Yonela Geja; Jon Barry; Yandiswa Mdazuka; Gcobani Mooi; Denise Doran; Freya Tooley; Rogan Harmer; Thomas Maes (Frontiers in Marine Science, 2020)

Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon ( Salmo salar ) - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)
This study was conducted to determine the effects of a co‐infection with Moritella viscosa at different exposure levels of sea lice Lepeophtheirus salmonis in Atlantic salmon ( Salmo salar ). M. viscosa (1.14 × 10 6 cfu/ml) was introduced to all experimental tanks at 10 days post‐lice infection (dpLs). Mean lice counts decreased over time in both the medium lice co‐infection (31.5 ± 19.0 at 7 dpLs; 16.9 ± 9.3 at 46 dpLs) and high lice co‐infection (62.0 ± 10.8 at 7 dpLs; 37.6 ± 11.3 at 46 dpLs). There were significantly higher mortalities and more severe skin lesions in the high lice co‐infected group compared to medium lice co‐infected group or M. viscosa ‐only infection. Quantitative gene expression analysis detected a significant upregulation of genes in skin from the high lice co‐infection group consistent with severe inflammation ( il‐8 , mmp‐9 , hep, saa ). Skin lesions retrieved throughout the study were positive for M. viscosa growth, but these were rarely located in regions associated with lice. These results suggest that while M. viscosa infection itself may induce skin lesion development in salmon, co‐infection with high numbers of lice can enhance this impact and significantly reduce the ability of these lesions to resolve, resulting in increased mortality.

Cover Image - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)

High Degree of Genetic Heterogeneity for Hereditary Cerebellar Ataxias in Australia - Ce Kang; Christina Liang; Kate E. Ahmad; Yufan Gu; Sue-Faye Siow; James G. Colebatch; Scott Whyte; Karl Ng; Philip D. Cremer; Alastair J. Corbett; Ryan L. Davis; Tony Roscioli; et al. (The Cerebellum, 2019)

Desiccation Resistance and Micro-Climate Adaptation: Cuticular Hydrocarbon Signatures of Different Argentine Ant Supercolonies Across California - Jan Buellesbach; Brian A. Whyte; Elizabeth Cash; Joshua D. Gibson; Kelsey J. Scheckel; Rebecca Sandidge; Neil D. Tsutsui (Journal of Chemical Ecology, 2018)

Current knowledge and breeding perspectives for the spider plant (Cleome gynandra L.): a potential for enhanced breeding of the plant in Africa - A. O. Kwarteng; J. Abogoom; R. Adu Amoah; D. Nyadanu; T. Ghunney; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; D. D. Asiedu; T. Whyte (Genetic Resources and Crop Evolution, 2018)

Current knowledge and breeding avenues to improve upon Frafra potato (Solenostemon rotundifolius (Poir.) J. K. Morton) - A. O. Kwarteng; T. Ghunney; R. Adu Amoah; D. Nyadanu; J. Abogoom; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; T. Whyte; D. D. Asiedu (Genetic Resources and Crop Evolution, 2018)

The impact of chronic endurance and resistance training upon the right ventricular phenotype in male athletes - Victor Utomi; David Oxborough; Euan Ashley; Rachel Lord; Sarah Fletcher; Mike Stembridge; Rob Shave; Martin D. Hoffman; Greg Whyte; John Somauroo; Sanjay Sharma; Keith George (European Journal of Applied Physiology, 2015)

Why dry? Investigating the future evolution of the Caribbean Low Level Jet to explain projected Caribbean drying - Michael A. Taylor; Felicia S. Whyte; Tannecia S. Stephenson; Jayaka D. Campbell (International Journal of Climatology, 2013)
Under global warming the Caribbean is projected to be significantly drier by century's end during its primary rainy season from May to November. The PRECIS regional model is used to simulate the end‐of‐century (2071–2100) manifestation of the Caribbean Low Level Jet (CLLJ) under two Intergovernmental Panel on Climate Change (IPCC) global warming scenarios. The CLLJ is a feature of the Intra‐American seas which during its July peak is dynamically linked to a brief mid‐summer drying and interruption of the Caribbean rainy season. The regional model captures the CLLJ's present‐day spatial and temporal characteristics reasonably well, simulating both the boreal winter (February) and summer (July) peaks. Under global warming there is an intensification of the CLLJ's core strength from May through November. The intensification is such that by October the CLLJ is of comparable core strength to its present‐day peak in July. The persistence of the strong CLLJ beyond July and through November is linked to the perpetuation of a dry pattern in the Caribbean in the future. In contrast, the boreal winter manifestation of the CLLJ is largely unaltered in the future. Copyright © 2012 Royal Meteorological Society

A fixed‐dose approach to conducting emamectin benzoate tolerance assessments on field‐collected sea lice, Lepeophtheirus salmonis - S K Whyte; J D Westcott; A Elmoslemany; K L Hammell; C W Revie (Journal of Fish Diseases, 2013)
In N ew B runswick, C anada, the sea louse, L epeophtheirus salmonis, poses an on‐going management challenge to the health and productivity of commercially cultured A tlantic salmon, S almo salar . While the in‐feed medication, emamectin benzoate ( SLICE ® ; M erck), has been highly effective for many years, evidence of increased tolerance has been observed in the field since late 2008. Although bioassays on motile stages are a common tool to monitor sea lice sensitivity to emamectin benzoate in field‐collected sea lice, they require the collection of large numbers of sea lice due to inherent natural variability in the gender and stage response to chemotherapeutants. In addition, sensitive instruments such as EC 50 analysis may be unnecessarily complex to characterize susceptibility subsequent to a significant observed decline in efficacy. This study proposes an adaptation of the traditional, dose–response format bioassay to a fixed‐dose method. Analysis of 657 bioassays on preadult and adult stages of sea lice over the period 2008–2011 indicated a population of sea lice in N ew B runswick with varying degrees of susceptibility to emamectin benzoate. A seasonal and spatial effect was observed in the robustness of genders and stages of sea lice, which suggest that mixing different genders and stages of lice within a single bioassay may result in pertinent information being overlooked. Poor survival of adult female lice in bioassays, particularly during M ay/ J une, indicates it may be prudent to consider excluding this stage from bioassays conducted at certain times of the year. This work demonstrates that fixed‐dose bioassays can be a valuable technique in detecting reduced sensitivity in sea lice populations with varying degrees of susceptibility to emamectin benzoate treatments.

Microbial diversity and activity in hypersaline high Arctic spring channels - Chih-Ying Lay; Nadia C. S. Mykytczuk; Thomas D. Niederberger; Christine Martineau; Charles W. Greer; Lyle G. Whyte (Extremophiles, 2012)

Future climate of the Caribbean from a regional climate model - Jayaka D. Campbell; Michael A. Taylor; Tannecia S. Stephenson; Rhodene A. Watson; Felicia S. Whyte (International Journal of Climatology, 2011)
Scenarios of rainfall and temperature changes for the period 2071–2100 under the A2 and B2 Special Report on Emissions scenarios are examined using the Hadley Centre Providing Regional Climates for Impacts Studies regional climate model. The model simulates ‘present‐day’ (1979–1990) rainfall and temperature climatologies reasonably well, capturing the characteristic bimodality of Caribbean rainfall and the boreal summer maximum and winter minimum temperatures. Seasonal spatial patterns are also reproduced, but rainfall amounts are underestimated over the northern Caribbean island masses, including Cuba, Jamaica, Hispaniola and Puerto Rico. Temperatures over the region are also overestimated by 1–3 °C. For the period 2071–2100, temperatures are projected to increase across the region by 1–4 °C for all months irrespective of the scenario. The rainfall response varies with season with one of the more robust changes being an intensification of a gradient pattern in November–January, in which the northern Caribbean (i.e. north of 22°N) gets wetter and the southern Caribbean gets drier. There is also a robust June–October drying signal. The results point to changes in the regional circulation patterns due to the human‐induced climate change and warrants further investigation. Copyright © 2010 Royal Meteorological Society

Cardiovascular function and the veteran athlete - M. Wilson; R. O’Hanlon; S. Basavarajaiah; K. George; D. Green; P. Ainslie; S. Sharma; S. Prasad; C. Murrell; D. Thijssen; A. Nevill; G. Whyte (European Journal of Applied Physiology, 2010)

Optimization of square-wave electroporation for transfection of porcine fetal fibroblasts - Jason W. Ross; Jeffrey J. Whyte; Jianguo Zhao; Melissa Samuel; Kevin D. Wells; Randall S. Prather (Transgenic Research, 2010)

Novel sulfur‐oxidizing streamers thriving in perennial cold saline springs of the Canadian high Arctic - Thomas D. Niederberger; Nancy N. Perreault; John R. Lawrence; Jay L. Nadeau; Randall E. Mielke; Charles W. Greer; Dale T. Andersen; Lyle G. Whyte (Environmental Microbiology, 2009)
Summary The perennial springs at Gypsum Hill (GH) and Colour Peak (CP), situated at nearly 80°N on Axel Heiberg Island in the Canadian high Arctic, are one of the few known examples of cold springs in thick permafrost on Earth. The springs emanate from deep saline aquifers and discharge cold anoxic brines rich in both sulfide and sulfate. Grey‐coloured microbial streamers form during the winter months in snow‐covered regions of the GH spring run‐off channels (−1.3°C to 6.9°C, ∼7.5% NaCl, 0–20 p.p.m. dissolved sulfide, 1 p.p.m. dissolved oxygen) but disappear during the Arctic summer. Culture‐ and molecular‐based analyses of the 16S rRNA gene (FISH, DGGE and clone libraries) indicated that the streamers were uniquely dominated by chemolithoautotrophic sulfur‐oxidizing Thiomicrospira species . The streamers oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions and a Thiomicrospira strain isolated from the streamers also actively oxidized sulfide and thiosulfate and fixed CO 2 under cold, saline conditions. Overall, the snow‐covered spring channels appear to represent a unique polar saline microhabitat that protects and allows Thiomicrospira streamers to form and flourish via chemolithoautrophic, phototrophic‐independent metabolism in a high Arctic winter environment characterized by air temperatures commonly below −40°C and with an annual average air temperature of −15°C. These results broaden our knowledge of the physical and chemical boundaries that define life on Earth and have astrobiological implications for the possibility of life existing under similar Martian conditions.

Features of the Caribbean low level jet - Felicia S. Whyte; Michael A. Taylor; Tannecia S. Stephenson; Jayaka D. Campbell (International Journal of Climatology, 2008)
The Caribbean Low Level Jet (CLLJ) is shown to be a real and dominant climatological feature of the early summer Caribbean climate. It manifests as an intensification in the trade winds in the western Caribbean basin (70°W–80°W) with an east‐west axis along 15°N. It is confined to heights below 600 mb and has maximum wind speeds approaching 16 m/s near the surface. The study shows that there is variability in the strength and zonal extent of the CLLJ which can be related to zonal SST gradients between the eastern equatorial Pacific and the north tropical and/or equatorial Atlantic. When the gradient is driven by the Pacific (as in an EL Niño event) the CLLJ winds are intensified to the north and in its southwesternmost quadrant. When the winds are driven by the tropical north Atlantic there is uniform wind intensification about the jet axis. The CLLJ is also linked to a precipitation maximum over the near waters and along the Caribbean coast of Central America (up to 16°N) during June and more so, in July. There is evidence of variation at the northern extent of this wet zone depending on the ocean basin forcing the SST gradient. The CLLJ is also linked to moderate drying in the main Caribbean basin. Copyright © 2007 Royal Meteorological Society

The effects of marathon running on expression of the complement regulatory proteins CD55 (DAF) and CD59 (MACIF) on red blood cells - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Natalie Middleton; Rob Shave; Keith George; Keith Guy (European Journal of Applied Physiology, 2006)

The effects of intensive, moderate and downhill treadmill running on human blood lymphocytes expressing the adhesion/activation molecules CD54 (ICAM-1), CD18 (β2 integrin) and CD53 - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Keith Guy (European Journal of Applied Physiology, 2006)

New sources of resistance to Radopholus similis in Musa germplasm from Asia - C. Dochez; J. Dusabe; J. Whyte; A. Tenkouano; R. Ortiz; D. De Waele (Australasian Plant Pathology, 2006)

The Effect of Creosote on Vitellogenin Production in Rainbow Trout (Oncorhynchus mykiss) - J. P. Sherry; J. J. Whyte; N. A. Karrow; A. Gamble; H. J. Boerman; N. C. Bol; D. G. Dixon; K. R. Solomon (Archives of Environmental Contamination and Toxicology, 2006)

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003 - O. M. Murphy; S. Murchan; D. Whyte; H. Humphreys; A. Rossney; P. Clarke; R. Cunney; C. Keane; L. E. Fenelon; D. O’Flanagan (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Cardiac drift during prolonged exercise with echocardiographic evidence of reduced diastolic function of the heart - E. A. Dawson; R. Shave; K George; G. Whyte; D. Ball; D. Gaze; P. Collinson (European Journal of Applied Physiology, 2005)

Effect of Maintaining Rainbow Trout in Creosote Microcosms on Lens Optical Properties and Liver 7-Ethoxyresorufin- O -Deethylase (EROD) Activity - J. J. Whyte; K. L. Herbert; N. A. Karrow; D. G. Dixon; J. G. Sivak; N. C. Bols (Archives of Environmental Contamination and Toxicology, 2000)